2014
DOI: 10.4161/cbt.29925
|View full text |Cite
|
Sign up to set email alerts
|

A novel small-molecule compound diaporine A inhibits non-small cell lung cancer growth by regulating miR-99a/mTOR signaling

Abstract: Abbreviations: NSCLC, non-small cell lung cancer; CDK, cyclin-dependent kinase; mTOR, mammalian target of rapamycin; p70S6K, ribosomal protein S6 kinase (70KD); CFSE, carboxyfluorescein diacetate succinimidyl ester; MK, midkine; miRNAs, microRNAsMicroRNas (miRNas) dysregulation is critically involved in lung cancer. Regulating miRNas by natural agents may be a new strategy for cancer treatment. We previously found that a novel small-molecule compound diaporine a (D261), a natural product of endophytic fungus 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Diaporine inhibited tumor growth in H460 xenograft mice. 136 Additional natural compounds such as curcumin, resveratrol, ori-donin, quercetin, fisetin, indole-3-carbinol, isoflavones and polygonatum cyrtonema lectin do not inhibit mTOR directly, but effect expression or activity via mTOR pathway signaling modulation. 137,138 …”
Section: Implication Of Targeting Mtor Signaling In Lung Cancermentioning
confidence: 99%
“…Diaporine inhibited tumor growth in H460 xenograft mice. 136 Additional natural compounds such as curcumin, resveratrol, ori-donin, quercetin, fisetin, indole-3-carbinol, isoflavones and polygonatum cyrtonema lectin do not inhibit mTOR directly, but effect expression or activity via mTOR pathway signaling modulation. 137,138 …”
Section: Implication Of Targeting Mtor Signaling In Lung Cancermentioning
confidence: 99%
“…10 The mammalian target of rapamycin (mTOR) signaling pathway plays a core role in regulating cell proliferation, motility and survival. 11 Previous reports have shown that mTOR stimulation is associated with fibrotic diseases, including cardiac, liver and kidney fibrosis. Gui et al proved that mTOR activation in alveolar epithelial cells and autophagy in the pulmonary is associated with the development of PF.…”
Section: Introductionmentioning
confidence: 99%
“…3,6-dihydroxyflavone, diaporine A (Saini et al, 2011;Chang et al, 2012;Xia et al, 2012;Song et al, 2014). However, there is still no related report about the effects of Andro on miRNA expression profile when it exerts its inhibition on hepatoma tumor growth.…”
Section: Accepted Manuscriptmentioning
confidence: 92%